Role of KDM2B epigenetic factor in regulating calcium signaling in prostate cancer cells - Evangelia Pantazaka; Saad Alkahtani; Saud Alarifi; Abdullah A. Alkahtane; Christos Stournaras; Galatea Kallergi (Saudi Pharmaceutical Journal)
KDM2B, a histone lysine demethylase, is expressed in a plethora of cancers. Earlier studies from our group, have showcased that overexpression of KDM2B in the human prostate cancer cell line DU-145 is associated with cell adhesion, actin reorganization, and improved cancer cell migration. In addition, we have previously examined changes of cytosolic Ca2+, regulated by the pore-forming proteins ORAI and the Ca2+ sensing stromal interaction molecules (STIM), via store-operated Ca2+ entry (SOCE) in wild-type DU-145. This study sought to evaluate the impact of KDM2B overexpression on the expression of key molecules (SGK1, Nhe1, Orai1, Stim1) and SOCE. Furthermore, this is the first study to evaluate KDM2B expression in circulating tumor cells (CTCs) from patients with prostate cancer. mRNA levels for SGK1, Nhe1, Orai1, and Stim1 were quantified by RT-PCR. Calcium signals were measured in KDM2B-overexpressing DU-145 cells, loaded with Fura-2. Blood samples from 22 prostate cancer cases were scrutinized for KDM2B expression using immunofluorescence staining and the VyCAP system. KDM2B overexpression in DU-145 cells increased Orai1, Stim1, and Nhe1 mRNA levels and significantly decreased Ca2+ release. KDM2B expression was examined in 22 prostate cancer patients. CTCs were identified in 45 % of these patients. 80 % of the cytokeratin (CK)-positive patients and 63 % of the total examined CTCs exhibited the (CK + KDM2B + CD45−) phenotype. To conclude, this study is the first to report increased expression of KDM2B in CTCs from patients with prostate cancer, bridging in vitro and preclinical assessments on the potentially crucial role of KDM2B on migration, invasiveness, and ultimately metastasis in prostate cancer.